Work Ability of Machinery Manufacturing Employees - Gergana Sandeva; Rositsa Deliradeva; Pavlina Gidikova (Journal of Biomedical & Clinical Research)
Assessment of work ability is an important aspect of occupational medical services, the main goal being to maintain employees’ health, well-being and efficiency. The aim of the study was to evaluate and compare the work ability of workers employed by two machinery factories. We used the Work Ability Index (WAI) questionnaire to assess 165 workers of an iron casting factory A and 166 workers in a press-forging plant B. The data obtained were evaluated and compared based on gender, age, length of service and occupation. Mean WAI for the two factories were almost identical (43.3±4.9 for Factory A and 43.3±4.6 for Factory B), both indicating good overall work ability. The lowest mean WAI (37.7) was registered for the crane operators from Factory B, and the highest (47.2) - for the molders in Factory A. The female production workers in Factory A had a significantly lower WAI as compared to their male counterparts (p=0.001). WAI also varied significantly between different age groups and occupations in the two plants. Significant negative correlations were found between work ability and length of service, as well as between psychological resources and gender (Factory A) and the length of service (Factory B). WAI is a useful tool in finding vulnerable workers who need more attention from occupational health specialists.